ARABIC LANGUAGE LEARNING PROGRAM MANAGEMENT AT DARUSSALAM GONTOR MODERN ISLAMIC BOARDING SCHOOL - Amalia, Jessica Noer; Mukhlis, M. Sholahudin; Makmur, Reynizqy Mughniza; Fikri, Shofil (Abjadia : International Journal of Education, 2024)
This study aims to deeply examine the management of Arabic language learning programs at Darussalam Gontor Modern Islamic Boarding School, based on management theory's stages of planning, organizing, implementing, and supervising. The research reveals a systematic and comprehensive approach to managing these programs, which includes a structured curriculum, daily use of Arabic, an immersive language environment, quality books and teaching materials, competent teachers, extracurricular activities, evaluations, examinations, and alumni involvement. Using qualitative methods, data were collected through observation, interviews, and documentation, and analyzed with the Miles and Huberman approach involving data reduction, presentation, and conclusion drawing. Triangulation ensured data validity and credibility. The study concludes that the management of Arabic language learning at Darussalam Gontor is highly effective and well-structured. Key supporting factors include intensive Arabic activities, the use of learning media, and the active involvement of teachers and students. However, the study also identifies inhibiting factors that need addressing to further enhance the program's effectiveness and efficiency.